2013
DOI: 10.1002/ijc.28422
|View full text |Cite
|
Sign up to set email alerts
|

Subclonal evolution of a classical Hodgkin lymphoma from a germinal center B‐cell‐derived mantle cell lymphoma

Abstract: Composite lymphomas (CL) represent the occurrence of two distinct lymphomas in the same patient. Often, CL share a common cellular origin, thus representing a unique model to investigate the multistep genetic path leading to lymphomagenesis in general and to the specific development of each distinct lymphoma component in particular. Here, we present the molecular analysis of a case consisting of an unusual Hodgkin lymphoma (HL) and a mantle cell lymphoma (MCL), intimately admixed within one another in lymph no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 53 publications
5
39
0
Order By: Relevance
“…In this study, functional yeast assays revealed the non-functionality of TP53 in three cell lines and DNA sequencing revealed the same mutations previously described in L1236, HDLM2, and L428 [ 21 ]. This re-evaluation of the TP53 status in HL using a sensitive technique reinforces the concept that TP53 mutation may be involved in the pathology of some cases of HL [ 29 ] and perhaps in the genomic instability observed in this disease, as well as the occurrence of late complications, such as secondary cancer following HL treatment [ 30 ] or HL as a secondary event [ 6 ]. It may be informative to investigate the TP53 status in lymph nodes derived from relapsing or refractory HL patients.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In this study, functional yeast assays revealed the non-functionality of TP53 in three cell lines and DNA sequencing revealed the same mutations previously described in L1236, HDLM2, and L428 [ 21 ]. This re-evaluation of the TP53 status in HL using a sensitive technique reinforces the concept that TP53 mutation may be involved in the pathology of some cases of HL [ 29 ] and perhaps in the genomic instability observed in this disease, as well as the occurrence of late complications, such as secondary cancer following HL treatment [ 30 ] or HL as a secondary event [ 6 ]. It may be informative to investigate the TP53 status in lymph nodes derived from relapsing or refractory HL patients.…”
Section: Discussionsupporting
confidence: 69%
“…The TP53 status of HL has been the subject of debate and remains controversial [ 21 ]. The lack of proven TP53 mutations in lymph nodes contrasts with the levels of its expression which are often high [ 6 ]. The disruption of this process can promote tumor progression and resistance to treatment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reevaluation of the P53 status in HL cell lines has demonstrated the presence of deletions within exon 4 in the L428 cell line and a nearly complete loss of exons 10–11 in the L1236 and exons 8–11 in the HDLM-2 cell lines. These data suggest that mutation of TP53 may be involved in the pathology of some cases of HL [ 53 ] and perhaps in the genomic instability observed during in the course of HL, as well as in the frequent occurrence of late complications, such as secondary cancer [ 54 ] or HL as a secondary event [ 55 ]. The correlation between TP53 status and high-grade progression in B-cell lymphoma has been previously established [ 56 , 57 ].…”
Section: Advances In the Understanding Of Molecular Mechanisms Of mentioning
confidence: 99%